Effect of online learning for dental education in asia during the pandemic of COVID-19 - Tsai-Yu Chang; Ming-Lun Hsu; Jae-Sung Kwon; MF.Lindawati S. Kusdhany; Guang Hong (Elsevier, 2021)
Background/purpose: Online learning has been utilized in the world to continue educational activities in dentistry, which was severely affected by the pandemic of coronavirus disease 2019 (COVID-19). The purpose of this study was aimed to evaluate the effect of online learning during the pandemic of COVID-19 in different dental schools of different countries in Asia by the questionnaire survey. Materials and methods: Mantel-Haenszel chi-square tests were used to analyze the difference between dental schools with and without shutdown. A questionnaire-based online survey was used to evaluate the online learning effect on undergraduate students in 13 dental schools of 7 Asia countries and regions. Results: For the question that blended learning class has better learning efficiency, the agreement rate was significantly higher in the students (80.3%) from the dental schools that did not suspend face-to-face education activities than in the students (50.3%) from the dental school that was shut down. Conclusion: Within the limitation of this study, it is concluded that a combination of physical and online classes in terms of blended learning courses will be the future trend for dental education.